Economic Boycott from the Islamic Law Perspective: A Post-Tūfān al-ʾAqṣā Case Study - Naim Hank (Trabzon İlahiyat Dergisi)

(untitled)
An economic boycott is a process that states, agencies, and ‎individuals use to cut off trade relations with another party, aiming to apply economic pressure. This research aims to define the concept of economic boycott from an Islamic perspective and its rulings. The study concentrates on the economic boycott that followed the Tūfān al-ʾAqṣā in Gaza and the subsequent increase in calls for the boycott of international corporations. A selection of prominent brands was examined to assess the financial impact of the boycott on the selected companies and to evaluate whether the objectives of Sharī‘ah were met while practicing boycotts. The inductive approach was employed to trace the opinions of jurists regarding the economic boycott as well as the commercial activities of the companies involved following the Tūfān al-ʾAqṣā. Additionally, the analytical approach was utilized to analyze this data and connect it to the concept of public interest within Islamic law. This research was based on economic statistics shared on the boycotted companies' websites. The data in question claims that the companies did not face a significant financial loss due to the boycott after the Tūfān al-ʾAqṣā. However, a control mechanism to verify this data could not be determined. While it can be said that the companies did not face a serious financial loss, more ‎sensitivity should be shown to calls for the boycott of such companies that potentially harm Muslims or support enemies ‎who commit genocide in places like Gaza. Since current boycott practices are insufficient to achieve the purposes aimed to be realized with the provisions regarding boycott in the Islamic Law system reached in the research. In addition, there are sufficient alternative products to meet consumer needs. This shows that ‎boycott calls cannot be neglected with unrealistic excuses.